Aerospace series. Cable outlet accessories for circular and rectangular electrical and optical connectors. Cable outlet, style A, 90°, unsealed, self-locking with clamp strain relief for EN 3645. Product standard Part 021, (30th April 2010) - British Standards Institution,
No abstract available